Under my skin - Unger, Lisa, 1970- (HQ Fiction, 2018)
It's been a year since Poppy's husband, Jack, was brutally murdered during his morning run through Manhattan's Riverside Park. In the immediate aftermath, Poppy spiralled into an oblivion of grief, disappearing for several days only to turn up ragged and confused and wearing a tight red dress she didn't recognise. What happened to Poppy during those lost days? And more importantly, what happened to Jack? The case was never solved, and Poppy has finally begun to move on. Then Poppy starts having nightmares and blackouts. When she begins to sense that someone is following her, Poppy is plunged into a game of cat and mouse, determined to unravel the mystery around her husband's death. But can she handle the truth about what really happened?